Answer:
x-2x = -3 and x = 3
Step-by-step explanation:
Given the expression
y=x+5.... 1
y-2x=2.... 2
Substituting the first equation into the second we will have;
From 2;
y -2x = 2
x+5-2x = 2
x-2x +5 = 2
x-2x = 2-5
x-2x = -3
-x =-3
x =3
Hence the required equation is x-2x = -3 and x = 3
so ya I don't see it, it must be crazy
Answer:
Y = -5/3x + 6 2/3
Step-by-step explanation:
Hope this helps. Pls give brainliest.
10+10+10=30 this might be right but i dont know
Answer:
60 Iris Blooms
Step-by-step explanation:
Find how much is 50% by multiplying 40*.50
You should get 20
Add 20 to 40 and get 60